2005
DOI: 10.1007/s00467-005-2058-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of prenatally detected primary vesicoureteral reflux

Abstract: The purpose of this study was to report the clinical course of medium-long-term follow-up of children with prenatally detected vesicoureteral reflux (VUR). Between 1986 and 2004, 53 (41 males) children with VUR detected by investigation of prenatal hydronephrosis were followed up for a mean time of 66 months (range: 6-200 months). Newborns were investigated by ultrasound, voiding cystourethrogram (VCUG) and DMSA scan. Follow-up clinical visits were performed at 6-month intervals. After 24 months patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…Other concerns about current diagnostic and therapeutic strategies include the cost and potential psychological harm of studies to detect VUR and its follow-up to resolution, 5, 11, 22, 23 and the development of antimicrobial resistance with long-term prophylactic antibiotic use 24, 25 . Doubts have arisen concerning the role of VUR in renal scarring and the efficacy of current therapeutic strategies in comparison to prompt evaluation and treatment of UTI 2, 7, 8, 26 .…”
Section: The Link Between Urinary Tract Infection and Vesicoureteral mentioning
confidence: 99%
See 2 more Smart Citations
“…Other concerns about current diagnostic and therapeutic strategies include the cost and potential psychological harm of studies to detect VUR and its follow-up to resolution, 5, 11, 22, 23 and the development of antimicrobial resistance with long-term prophylactic antibiotic use 24, 25 . Doubts have arisen concerning the role of VUR in renal scarring and the efficacy of current therapeutic strategies in comparison to prompt evaluation and treatment of UTI 2, 7, 8, 26 .…”
Section: The Link Between Urinary Tract Infection and Vesicoureteral mentioning
confidence: 99%
“…Another issue for consideration is that primary VUR may be discovered during follow-up investigations for prenatal ultrasound findings or after a UTI 8, 26, 31 . Because our interest is in patients with primary rather than secondary VUR, the timing of the discovery of reflux is less important.…”
Section: B Vesicoureteral Reflux (Vur)mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the children (501 out of 549; 91.3%) were admitted after the first episode of urinary tract infection. The remaining 48 patients had antenatal hydronephrosis and no episode of urinary tract infection had occurred when the diagnosis of VUR was established 12 . In our series, the median age at diagnosis of the first urinary tract infection was 8.9 months (interquartile range (IQ), 4.4–20.3 months) and the median age at diagnosis of VUR was 19 months (IQ, 9–38 months).…”
Section: Methodsmentioning
confidence: 73%
“…Nevertheless, VUR increases the risk of post‐pyelonephritic renal scars in children 8,9 . On the other hand, data from series of VUR obtained in the investigation of foetal hydronephrosis have shown that renal damage can occur in the absence of infection 10–12 . Therefore, when considering the pathogenesis of renal damage, it is essential to distinguish between the acquired segmental scarring associated with VUR and infection and the primary renal damage seen congenitally whose aetiology is very different and linked to abnormal metanephric development 4,13 …”
mentioning
confidence: 99%